Potential Role of CD47-Directed Bispecific Antibodies in Cancer Immunotherapy - Yang, Yan; Yang, Zheng; Yang, Yun (Frontiers in Immunology, 2021)
The success of cancer immunotherapy has generated enormous interest in identifying new immunotherapeutic targets. After the approval of blinatumomab, a CD19-targeted bispecific antibody for acute lymphoblastic leukemia, several CD47-targeted bispecific antibodies for cancer immunotherapy are being investigated in clinical trials. In this review article of CD47-targeted bispecific antibodies, we described the rationale for bispecific antibodies, summarized the data from four ongoing phase I studies, reviewed the major toxicities associated with CD47-targeted bispecific antibody therapy of on-target toxicity to healthy cells and a pronounced antigen-sink, and described possible mechanisms of resistance to CD47-targeted bispecific antibody therapy. Further clinical studies are expected to fully validate its safety and effectiveness in patients.